IMPROVING STUDENTSâ€™ COMPETENCE IN WRITING DESCRIPTIVE TEXTS THROUGH â€œFRESHâ€ TECHNIQUE - Faisal Aulia; Yasinta Wulandari (English Review: Journal of English Education, 2013)
Abstract: This research was aimed to know whether â€œFRESHâ€ technique can improve studentsâ€™ competence in writing descriptive texts. This research was conducted in one of the junior high schools in Banyumas in academic year 2012/2013. The method of this research is Classroom Action Research (CAR). The research participants were the students of VIII E class consisting of 28 students. The treatment was carried out in two cycles of four actions, from November 9th, 2012 to December 1st, 2012. The quantitative data (tests) were evaluated by using Burhan Nurgiyantoroâ€™s Writing Evaluation Criteria which consisted of evaluation in content, organization, vocabulary, language, and mechanics. Based on the data analysis, it could be described that the studentsâ€™ competence in writing descriptive texts improved. It could be seen from the improvement of studentsâ€™ score in pre-test and post test. The improvement of studentsâ€™ score was 23.607%. This meant that â€œFRESHâ€ technique improved the studentsâ€™ competence in writing descriptive text in the eighth grade students of in academic year 2012/2013.Keywords: descriptive text, FRESH Technique, Classroom Action Research, writing competence